2020
DOI: 10.1021/acs.est.9b05767
|View full text |Cite
|
Sign up to set email alerts
|

Multiphase Chemistry Controls Inorganic Chlorinated and Nitrogenated Compounds in Indoor Air during Bleach Cleaning

Abstract: We report elevated levels of gaseous inorganic chlorinated and nitrogenated compounds in indoor air while cleaning with a commercial bleach solution during the House Observations of Microbial and Environmental Chemistry field campaign in summer 2018. Hypochlorous acid (HOCl), chlorine (Cl2), and nitryl chloride (ClNO2) reached part-per-billion by volume levels indoors during bleach cleaningseveral orders of magnitude higher than typically measured in the outdoor atmosphere. Kinetic modeling revealed that mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
207
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(226 citation statements)
references
References 66 publications
14
207
1
Order By: Relevance
“…100 For example, from this combination of the state-of-the-art measurements with kinetic modeling, it was revealed that multiphase chemistry drives inorganic chlorinated and nitrogenated compounds in indoor air during bleach cleaning. 67 Overall, as greater emphasis is placed on understanding the surface as an active participant in indoor chemistry, and not simply as an unknown entity that is a host to multiphase chemistry, the overall understanding of the chemistry of indoor environments and impacts on human health will improve. Central to improving the understanding of reactions occurring at surfaces are efforts to characterize the surfaces being probed, the use of standard surfaces across different indoor experiments to provide intercomparability and the understanding of the factors that drive surface chemistry.…”
Section: Emerging Methods For Investigating Indoor Surfacesmentioning
confidence: 99%
See 2 more Smart Citations
“…100 For example, from this combination of the state-of-the-art measurements with kinetic modeling, it was revealed that multiphase chemistry drives inorganic chlorinated and nitrogenated compounds in indoor air during bleach cleaning. 67 Overall, as greater emphasis is placed on understanding the surface as an active participant in indoor chemistry, and not simply as an unknown entity that is a host to multiphase chemistry, the overall understanding of the chemistry of indoor environments and impacts on human health will improve. Central to improving the understanding of reactions occurring at surfaces are efforts to characterize the surfaces being probed, the use of standard surfaces across different indoor experiments to provide intercomparability and the understanding of the factors that drive surface chemistry.…”
Section: Emerging Methods For Investigating Indoor Surfacesmentioning
confidence: 99%
“…These HOCl-dominated formation pathways become far more important indoors than outdoors and have been shown to impact the overall indoor oxidant budgets. 66 , 67 These halogen oxidants subsequently react with organic films 68 and with VOCs to form aerosols that provide further surface area for indoor reactions. 69 For example, HOCl can react with unsaturated molecules to form chlorohydrins ( Equation 5 ).…”
Section: Gas-phase Reactants and Their Interactions With Surfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…House cleaning is a pollution culprit as well. When using a commercial bleach solution, the researchers measured new ultrafine (<100 nm in diameter) particle formation and elevated levels of chlorine-containing gases (6). "This is evidence that there are chemical transformations occurring on quite rapid timescales in the indoor environment," says Farmer.…”
Section: What's Cookingmentioning
confidence: 99%
“…Two important effective chlorine species from bleach are chlorine (Cl 2 ) and hypochlorous acid (HOCl); recent studies have reported that concentrations of both these gases in indoor air significantly increased while using commercial bleach, with concentrations of Cl 2 and HOCl reaching 20‐25 and 50‐250 of ppbv, respectively 6,7 . Acute inhalation of these gases generally causes health problems such as reactive airways dysfunction syndrome (RADS) owing to Cl 2 gas generation from bleach use, especially when bleach mixes with acidic solutions such as hydrochloric acid (HCl) and vinegar 8‐10 .…”
Section: Introductionmentioning
confidence: 99%